Cross – sectional study of respiratory pathogens and their antibiotic susceptibility pattern in Tribhuvan University Teaching Hospital - Shrestha, U; Singh, A; Pokhrel, BM (Journal of Institute of Medicine Nepal, 2007)
Background: Lower respiratory tract infection (LRTI) comprises an array of diseases ranging from bronchitis to pneumonia; its asperity can sway from non-pneumonic LRTI to pneumonia or chronic obstructive pulmonary disease (COPD). The HMG/WHO review in 1994 estimated the overall acute respiratory infections in Nepal to be 2.1%. Methods: In brief, all total 132 sputum samples of patients suspected of LRTI those visiting Tribhuvan University Teaching Hospital during March to May 2005 were investigated with the use of standard microbiological methods and the bacterial isolates were subjected for antibiotic sensitivity test. Results: Of the total, 31.0% sputum samples showed significant positive. Among them75.6% were gram-negative bacteria (GNB) and 24.40% gram-positive bacteria (GPB). Eight different types of bacteria were isolated. Haemophilus influenzae (19.51%), Klebsiella pnemoniae (19.51%), Pseudomonas aeruginosa (19.51%), were the most common isolates followed by Streptococcus pneumoniae (12.19%), Staphylococcus aureus (12.19%), Escherichia coli (9.75 %), Citrobacter fruendii (4.87%), Acinetobacter calcoaceticus (2.43%). Antibiotic susceptibility test showed that, more than 50%ofGPBwere resistant to Erythromycin, Cephalexin and Ciprofloxacin whereas majority ofGNB were resistant to Ciprofloxacin, Gentamycin, Ampicillin. Conclusion: This study needs to be conducted round the year to acquire more information regarding seasonal variation. Key words: LRTI, Antibiotic susceptibility pattern, Sputum, GPB, GNB The full text of this paper is available at Journal of Institute of Medicine website